Nanoemulsion Formulation Combination of Virgin Coconut Oil (VCO) and Candlenut Oil (Alleurites mollucanus) for Hair Growth in Male White Rats (Rattus novergicus) - Lasanudin, Rindi Ibrahim; Bachri, Mochamad Saiful; Wahyuningsih, Iis; Efiana, Nur Ari (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Having healthy and thick hair is the dream of many people, but some people have problems related to their hair. Hair problems that often occur are hair loss, thin hair or baldness, so to overcome these problems hair growth products have been made. Virgin Coconut Oil VCO and candlenut oil can be used as natural ingredients that can grow hair. The aim of this research was to determine the best nanoemulsion formulation for a combination of candlenut oil and VCO; and to determine the difference between applying nanoemulsion, conventional candlenut oil, conventional VCO and the oil emulsion on hair growth in male rats. This nanoemulsion formulation uses a combination of candlenut oil and VCO in a ratio of 1:1, 1:3 and 3:1. The nanoemulsion obtained was subjected to organoleptic, pH, viscosity, flow type and % transmittance. The best formulation was then tested for droplet size and zeta potential as well as hair growth activity tests using male rats. It was found that the best nanoemulsion formula was a nanoemulsion with a combination of 1:3 with a yellow color, a distinctive odor and clear with a droplet size of 14.42 ± 0.03 nm, a zeta value of -27.8 ± 1.02 mV, the length of the hair produced in the test hair growth activity was 17.14 ± 0.42 mm and hair weight was 699.37 ± 7.91 mg.